Quassinoids from Eurycoma longifolia - Huyen, Le Thi; Nhiem, Nguyen Xuan; Thu, Vu Kim; Tai, Bui Huu; Tuan Anh, Hoang Le; Yen, Pham Hai; Trang, Do Thi; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
By various chromatographic separations, three quassinoids, pasakbumin-C (1), 13α,21-epoxyeurycomanone (2), and eurylactone A (3) were isolated from the methanol extract of the roots of E. longifolia. Their structures were determined by 1D-NMR, 2D-NMR and in comparison with literature data.